The 1%, Exploitation and Wealth: Tim Di Muzio interviews Shimshon Bichler and Jonathan Nitzan - Shimshon Bichler; Jonathan Nitzan; Tim Di Muzio (Review of Capital as Power, 2012)
Rethinking resistance, power and production.
Keywords: 330; capital; class; exploitation; labour power; Occupy Wall Street; productivity; resistance; wage; wealth